My Xbox : Xbox 360, Kinect, and Xbox LIVE - Loguidice, Bill (Que Pub., 2012)
This is the quick, visual, one-stop tutorial for everyone who wants to get maximum fun and entertainment out of their Xbox 360, Xbox Live, and Kinect controller. Gaming experts Christina and Bill Loguidice cover everything Xbox has to offer, uncovering cool features and tools most users won't ever discover on their own. You learn how to get started with Xbox 360; fast-network your Xbox 360s; run the media content in your Windows PCs; personalize your Xbox experiences; find great stuff on Microsoft's Game, Video, and Music Marketplaces; get acquainted with your Xbox friends and communities; get to know the Kinect controller and Hub; and find great Kinect games and get better at playing them. This book's concise, step-by-step instructions link to callouts on Xbox screen captures that show you exactly what to do. Tips and Notes help you discover powerful new techniques and shortcuts, and Help features guide you past common problems. This book is designed for all 50,000,000 Xbox 360 owners: from those who've just purchased their first system, to those diving headfirst into Kinect gaming, to millions of Xbox Live subscribers who want to get even more out of Microsoft's online services.